Human cytomegalovirus major immediate early transcripts arise predominantly from the canonical major immediate early promoter in reactivating progenitor-derived dendritic cells. (4th June 2020) - Mason, Rebecca; Groves, Ian J.; Wills, Mark R.; Sinclair, John H.; Reeves, Matthew B.
Abstract : Human cytomegalovirus latency and reactivation is a major source of morbidity in immune-suppressed patient populations. Lifelong latent infections are established in CD34+progenitor cells in the bone marrow, which are hallmarked by a lack of major lytic gene expression, genome replication and virus production. A number of studies have shown that inhibition of the major immediate early promoter (MIEP) – the promoter that regulates immediate early (IE) gene expression – is important for the establishment of latency and that, by extension, reactivation requires reversal of this repression of the MIEP. The identification of novel promoters (termed ip1 and ip2) downstream of the MIEP that can drive IE gene expression has led to speculation over the precise role of the MIEP in reactivation. In this study we show that IE transcripts arise from both the MIEP and ip2 promoter in the THP1 cell macrophage cell line and also CD14+monocytes stimulated with phorbol ester. In contrast, we show that in in vitro generated dendritic cells or macrophages that support HCMV reactivation IE transcripts arise predominantly from the MIEP and not the intronic promoters. Furthermore, inhibition of histone modifying enzyme activity confirms the view that the MIEP is predominantly regulated by the activity of cellular chromatin. Finally, we observe that ip2-derived IE transcription is cycloheximide-sensitive in reactivating DCs, behaviour consistent with an early gene designation. Taken together, these data argue that MIEP activity is still important for HCMV reactivation but ip2 activity could play cell-type-specific roles in reactivation.